River as a common good – the case of Wrocław - Adamiczka, Hanna (Rzeka jako dobro wspólne – studium przypadku Wrocławia, 2020)
Social participation is guaranteed by law; it enables citizens to decide on activities in a city. The article aims to examine the efficacy of participation in the decision-making process regarding river management in Wrocław. The author analysed to what extent the city’s inhabitants are involved in river management and what opportunities for self-government are provided for it. The methods: literature and document analysis, deduction, and statistical methods. The article discusses: the assumptions of participation, possibilities related to river management in Wrocław, data related to the inhabitants’ activity in the field of rivers and the forms of this activity. Results: residents are involved in river management if they are encouraged to do so; policy-makers are introducing tools that engage residents, but they are not always enough. The results may provide an introduction to research on participation tools that would encourage residents to engage in complex topics
Biblioteka Regionalisty, 2020, Nr 20, s. 7-19
Keywords: Wrocław (woj. dolnośląskie); river; participation; rzeka; partycypacja